The “State” and the “Political” in the Evolution of Pierre Clastres’ Thought: a Politological Reading - Filippo Benedetti (Scienza & Politica, 2023)
According to anthropologist Pierre Clastres, State and politics have always been seized, in Western culture, as two necessarily connected concepts – State is a political entity, there is no politics without the State. His studies try to de-construct this paradigm by considering primitive societies as societies without and against the State. This paper examines Clastres’ texts seeking to contextualise his thought within frameworks of legal and political sciences, demonstrating so that political anthropology and political sciences have strong epistemological links.